Incorporation of Inorganic Carbon Nanotubes Fillers into the CA Polymeric Matrix for Improvement in CO2/N2 Separation - Jawad, Z.A.; Ahmad, A.L.; Low, S.C.; Zein, S.H.S. (Current Nanoscience, 2015)
Among all separation techniques, membrane technology has been shown to reduce CO2 emissions without any phase changes due to its rapid, energy efficient process. The membrane-based gas separation must consist of a defect-free, thin, dense skin layer that is supported by a porous sub-layer that allows an excellent permeation rate and selectivity. This study is aimed at developing a defect-free, thin-skinned layer of mixed matrix membrane (MMM) from cellulose acetate (CA) polymer and functionalized multi walled carbon nanotubes (MWCNTs) as inorganic filler. The influences of membrane casting thickness (150-300) µm and CA polymer concentration (7-17) wt.% on membrane morphologies were first investigated. The outcome of these dominant parameters were then used to synthesize the MMM. The results showed that the defect-free, thin, dense skin thickness of membrane could be achieved with a casting thickness of 250 µm and CA polymer concentration of 10 wt.%. By considering both dominant parameters, the synthesized MMM proved to have a thin selective layer, whereby it showed a high permeance and selectivity for CO2/N2 gas separation.
Keywords: characterization